2021
DOI: 10.1016/j.gene.2020.145119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognosis-related genes in the cervical cancer immune microenvironment

Abstract: Background Cervical cancer is the fourth most common cancer in women worldwide. The metastasis and invasion of this type of cancer are closely related to the tumor microenvironment. Immune cells and stromal cells dominate the tumor microenvironment in cervical cancer. Therefore, we should further understand the association between tumor progress and immune cells or stromal cells. Methods we downloaded the gene expression profiles and clinical data of 307 patients with cervical cancers based on the TCGA databas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…However, the current understanding remains unsatisfactory and insufficient. Numerous previous research studies concentrated mainly on the RNA-seq profiles, which are characterized by some disadvantages in comprehensively clarifying the potential mechanisms involved ( Sun et al, 2019 ; Liu et al, 2020 ; Ma J. et al, 2020 ; Zhao et al, 2020 ; Yang et al, 2021 ). Many researchers have recently concentrated on investigating prognostic factors by integrative multi-omics data analysis, which yielded more powerful results and provided a more comprehensive view of the TME ( Gu et al, 2020 ; Ma H. et al, 2020 ; Yan et al, 2020 ; Zhang Y. et al, 2020 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current understanding remains unsatisfactory and insufficient. Numerous previous research studies concentrated mainly on the RNA-seq profiles, which are characterized by some disadvantages in comprehensively clarifying the potential mechanisms involved ( Sun et al, 2019 ; Liu et al, 2020 ; Ma J. et al, 2020 ; Zhao et al, 2020 ; Yang et al, 2021 ). Many researchers have recently concentrated on investigating prognostic factors by integrative multi-omics data analysis, which yielded more powerful results and provided a more comprehensive view of the TME ( Gu et al, 2020 ; Ma H. et al, 2020 ; Yan et al, 2020 ; Zhang Y. et al, 2020 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidences show that TIME is closely related to the development of cervical carcinoma and has an important value in OS or the prognosis of cervical carcinoma [5,7]. Emerging evidence has elucidated that tumors can act as distinct immunological organs with complex TIME, and the immune cells recruited and activated in TIME are linked to the malignant phenotypes of tumors [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently reports showed that the metastasis and invasion of cervical carcinoma are closely related to the tumor immune microenvironment (TIME), and targeted therapy for its TIME has been more and more developed and applied [5][6][7][8]. The cervical carcinoma progresses in TIME mainly composed of infiltrating immune and stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yuan et al [22] found that, the low expression of CD1B was related to the deterioration of lung adenocarcinoma. Compared with CD1B, CD1E is less studied, except that Yang et al [23] found that CD1E could be used as a prognostic indicator of cervical cancer. Similar results to our study was that, CD1B and CD1E could be used as prognostic indicators of TETs, and the low expression levels might be related to the poor prognosis.…”
Section: Discussionmentioning
confidence: 99%